Rotifer fauna of Seli Stream (Elazig-Turkey) and analysis with some biodiversity indexes - Ipek, Necla; Saler, Serap (Ege Univ, 2008)
For the aim of to determine rotifer fauna and their seasonal variations of Seli Stream (Elazig) rotifer samples have been collected from 5 station at monthly periods between March 2006 - February 2007. During the study, 13 Rotifera species were recorded. Polyarthra vulgaris and Kelicottia longispina were recorded as dominant species. Furthermore, some physical and chemical features of Seli Stream, the distrubition of Rotifera according to the stations, months, seasons and also some statistical parameters are given. The data obtained from the rotifera fauna of Seli Stream were analysed by Shannon-Weaver Diversity Index and Margalef Species Richness Index. Spring had got highest species diversity (H'= 2.38) and richness(D=2.6).
Keywords: Seli Stream; rotifera; seasonal variations; Shannon-Weaver; biodiversity indexes